Gender Disparities in Financial Literacy: A Comparative Study of Male and Female Residents in Helambu Rural Municipality, Bagmati Province - Shrestha, Ranu Maiya; Adhikari, Reena; Thapa, Chandra Bahadur; Adhikari, Samyog (AMC Journal (Dhangadhi), 2026)
This study examines gender differences in the financial literacy of adult residents of the Helambu Rural Municipality in Sindhupalchok District, Bagmati Province in Nepal. The primary data were collected using a structured questionnaire based on the OECD/INFE financial literacy toolkit, and 385 participants (196 males and 189 females) were selected to complete it based on a cross-sectional descriptive and analytic research design. There were three main dimensions that were measured by the instrument, including financial knowledge, financial behaviour, and financial attitude. The statistical analyses involved descriptive statistics, independent samples t-tests, and multiple linear regression models. The results show that the gender gap in the general scores of financial literacy is statistically significant (male = 64.38, SD = 11.52; female = 55.74, SD = 13.67; t = 6.89, p < 0.001). The difference was highest in the financial knowledge dimension, with a male-female difference of 12.46 percentage points then financial behaviour (6.28 points) and financial attitude(3.92 points). The regression analysis also ratified gender as an important predictor of financial literacy when other factors, such as age, education, income, and occupation, were adjusted. These findings reinforce the necessity of gender-specific financial literacy programs in rural Nepal municipalities, specifically, the need to increase the level of financial literacy among women and their participation in the financial decision-making of their households.